Imagens e imaginários: a criação da visão hegemônica de arquitetura moderna no Brasil - Cury, Laura de Souza (2022)
This dissertation aims to analyze how the hegemonic discourse about modern Brazilian architecture was created via photographic representations in exhibitions and in the printed media. A historical perspective is privileged in order to identify a sense of modernity in the works and the way in which this visuality, as well as an ideology of modernity and progress, could be created and disseminated through architectural and photographic representations, which were able to compose narratives and legitimize political actions in Brazil, creating a renewed “image” related to notions of progress and modernity for the country in the middle of the 20th century